Microfluídica de gotas para o encapsulamento de esferoides de células-tronco em alginato para regeneração tecidual - Mesquita, Cristiane Raquel Sousa (2019)
The chemical, biochemical and mass transfer / heat transfer analysis in segmented droplets, of the droplets type, in microfluidic devices presents more efficiency due to some of its characteristics such as large surface area and monodisperse sizes. Thus, the use of microfluidic systems for encapsulation of spheroids is a promising field because it exhibits important properties such as distribution of controlled and uniform droplet sizes, as well as their relative simplicity and reproducibility, which is not presented in traditional processes. The use of these spheroids encapsulated by hydrogel composite matrices are widely used in regenerative medicine, mainly due to the increase in surface area. Therefore, the present study presents the fabrication and testing of microfluidic devices, the formation of single emulsion droplets and, consequently, the encapsulation of spheroids in separate aqueous microdroplets dispersed in an immiscible carrier oil. Variations in the flow of dispersed and continuous phases are observed generating droplets with diameters varying from 335 ± 1 μm to 733 ± 15 μm, showing that the average size and morphology of the droplets vary with the viscosity and configuration of the capillaries. The encapsulation of spheroids in alginate hydrogels provides a simple and rapid tool for preparing microdroplets for systems related to regenerative medicine.